O som do silêncio e o silêncio do som: pela construção de uma sociologia sonora - Alves, Tiago Fernandes (2017)
The sonorous world is silenced by visual imperativeness of experiences and perceptions from the social and scientific world. The word experimentation in science is directly related to the observation process as collection and analysis of data. The participant observation, documentary and statistics analysis, as well as the description of the researched field always goes through visual field. The researcher's speech is the written word, therefore, mute, silenced. In this regard, this work seeks to grasp the social reality through sounds produced by interactions and conflicts present on it. In order to do so, we seek the construction of a theoretical field and methodological processes that make intelligible the process of elaboration of places and sonorous field as important effective places for sociological perspectives. This present study aimed to demonstrate the instruments and data collection techniques through sound ethnography through recordings of sounds on urban spaces and measurements of intensities in decibels values through a decibel meter. However, a documentary analysis was carried out to understand how the institutions and the State govern the sound spaces by delimiting the decibel emission values at the corresponding times and places. The results show the new meaning of sounds, as well as the production of high levels of decibels as forms of power disputes in the construction of spaces and sound fields. The relationship between sound, silence and noise involves a complex perception that goes beyond the subjective through institutional control policy bias on groups and individuals. Therefore, sound violence pervades both the modes of production of high decibel rates, as the silencing process, in which urban centers noise and individualization/atomization of individuals through acoustic isolation, reverberate in public spaces without political effective participation. Cities start to have its public spaces of political intervention silenced both by excesses of sound and individualistic ideology of sound isolation.